The Effect Of Service Quality And Price Toward Customer Satisfaction In Spa Services At Emi Salon Of Seluma Regency - Sherly Gustianti; Eska Prima Monique Damarsiwi; Yesi Indian Ariska (Journal of Indonesian Management, 2021)
The sample in this study was 50 customers of Emi Salon of Seluma Regency. The sampling technique is accidental sampling technique. The data were collected using a questionnaire and the analytical method used was multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 2.465 + 0.353X1 + 0.519 X2 + e, the coefficient of determination of adjust R square is 0.708. This means that X1 (service quality) and X2 (price), have a contribution to customer satisfaction (Y) of 70.8% while the remaining 29.2% is influenced by other variables not examined in this study. Service quality has a partially significant effect on consumer satisfaction at Emi Salon in Seluma Regency, this is evidenced by a significant value of 0.000 <0.05. Price has a partially significant effect on consumer satisfaction at Emi Salon Seluma Regency, this is evidenced by a significant value of 0.000 <0.05. Service quality and price have a significant effect simultaneously on consumer satisfaction at Emi Salon of Seluma Regency, this is evidenced by a significant value of 0.000 <0.05